The Effect of Discrimination on the Daily Life Satisfaction of People with Developmental Disability: Parallel Multiple Mediating Effect of Social Involvement and Self-Esteem - Jinhyeok Choi; Byeolhae Shin; Bum-Sung Choi (Medicina, 2023)
Background and Objectives: People with developmental disabilities are exposed to discrimination and it affects their daily life satisfaction. The purpose of this study is to examine the parallel mediating effect of social involvement and self-esteem on the relationship between discrimination and the daily life satisfaction of people with developmental disabilities to improve their daily life satisfaction. Materials and Methods: This study used raw data of participants with intellectual disabilities and autism spectrum disorder from a national panel survey of employment for the disabled second-wave fifth survey. First, correlations among variables were identified to determine whether variables are in a relationship, and then PROCESS Macro was conducted to identify the relationship between discrimination and daily life satisfaction and the parallel mediating effect of social involvement and self-esteem. Results: Discrimination had a significant negative effect on daily life satisfaction and it was found that social involvement and self-esteem have a significant mediating effect that lowers the effect size of discrimination on daily life satisfaction. Specifically, it was found that self-esteem had a more mediating effect than social involvement. Conclusions: To increase the daily life satisfaction of people with developmental disabilities, the potential need to not only decrease discrimination but also increase their social involvement and self-esteem should be considered.